2009
DOI: 10.1158/1078-0432.ccr-09-1521
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Characterization of the QTc Interval in Patients with Advanced Solid Tumors: Pharmacokinetic- Pharmacodynamic Evaluation of Sunitinib

Abstract: Purpose: To evaluate the effects of sunitinib, a multitargeted tyrosine kinase inhibitor, on the QT interval in patients with cancer. Experimental Design: Patients received sunitinib loading doses (150-200 mg) on days 3 and 9 and maintenance doses (50 mg/d) on days 4 to 8. Moxifloxacin (day 1), placebo (day 2), and granisetron [with placebo (day 2) or sunitinib (days 3 and 9)] were also administered. Treatment effects were evaluated by time-matched, serial electrocardiograms, and manually overread. Results: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 31 publications
3
69
0
3
Order By: Relevance
“…Therefore, cardiotoxicity is an established safety concern with the use of anticancer agents designed to target this particular pathway, including the anti-HER2 monoclonal antibody trastuzumab [11,12] and the anti-HER2/EGFR TKI lapatinib [13]. The cardiac adverse event (AE) profile of molecularly targeted agents, including the aforementioned anti-HER2 therapies and multitargeted smallmolecule TKIs, such as sunitinib, primarily consists of symptomatic or asymptomatic declines in left ventricular ejection fraction (LVEF) or alterations in blood pressure, with prolongation of the corrected QT interval and cardiac dysrhythmias as additional risks [14][15][16][17]. Cardiac AEs reported with these newer agents are typically low-grade and reversible, including LVEF reductions [18,19] and blood pressure elevations with or without secondary or end-organ involvement [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cardiotoxicity is an established safety concern with the use of anticancer agents designed to target this particular pathway, including the anti-HER2 monoclonal antibody trastuzumab [11,12] and the anti-HER2/EGFR TKI lapatinib [13]. The cardiac adverse event (AE) profile of molecularly targeted agents, including the aforementioned anti-HER2 therapies and multitargeted smallmolecule TKIs, such as sunitinib, primarily consists of symptomatic or asymptomatic declines in left ventricular ejection fraction (LVEF) or alterations in blood pressure, with prolongation of the corrected QT interval and cardiac dysrhythmias as additional risks [14][15][16][17]. Cardiac AEs reported with these newer agents are typically low-grade and reversible, including LVEF reductions [18,19] and blood pressure elevations with or without secondary or end-organ involvement [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vandetanib, which inhibits VEGFR and epidermal growth factor receptor signaling, significantly prolonged QTc interval [8]. An evaluation of sunitinib, a multitargeted tyrosine kinase inhibitor, demonstrated a dose-dependent effect on QT interval [9]. Based on the overall assessment, this study demonstrated that ramucirumab at a dose of 10 mg/kg administered every 21 days for 3 cycles did not produce a prolongation of QTcF.…”
Section: Study Completed Pharmacokinetics / Pharmacodynamicsmentioning
confidence: 70%
“…This abnormality was not associated with any clinical problems. In none of the patients was the QT longer than > 500 ms [19]. It is important that sunitinib has a binding affinity to 5HT2a serotonin receptors, alpha and beta adrenergic receptors, hERG receptor protein and Purkinje fibres; blocking them all, which may affect repolarisation.…”
Section: Prolonged Qt Interval -Tyrosine Kinase Inhibitorsmentioning
confidence: 97%